Digital Narcissism on Social Media: A Communication Science Perspective on Online Validation Culture (Journal of Dialogos, 2026)
This study examines the phenomenon of digital narcissism on social media platforms through the lens of communication science, with particular focus on the culture of online validation-seeking that has emerged in contemporary digital ecosystems. The increasing proliferation of social media has given rise to new behavioral patterns in which individuals engage in self-promotional activities driven by a desire for social approval, recognition, and affirmation from online audiences. Drawing on theoretical frameworks including Uses and Gratifications Theory, Social Comparison Theory, and Self-Presentation Theory, this paper analyzes how algorithmic mechanisms, platform affordances, and cultural factors collectively contribute to the amplification of narcissistic tendencies in digital environments. The study employs a systematic literature review methodology, synthesizing empirical findings from 20 peer-reviewed sources published between 2021 and 2023. Findings indicate that online validation culture manifests through selfie-posting, status broadcasting, and curated self-presentation, with significant variation across platforms. The study further reveals that excessive engagement in validation-seeking behaviors correlates with reduced psychological well-being, increased social comparison, and susceptibility to misinformation. The paper concludes with implications for communication practitioners, platform designers, and mental health advocates, urging the development of healthier digital engagement norms.